Relationship of teacher interaction and self-esteem with perception on baby dumping behavior among multi-ethnic secondary school students in Sabah - Balan Rathakrishnan; Murnizam Hj Halik; Sreehari Ravindranath (2013)
The study aims to examine the relationship between teacher interaction and self-esteem with perception on baby dumping behavior among multi-ethnic secondary school students in Sabah. A total of 781 middle school students from diverse ethnic groups have taken part in this survey. This survey study conducted by questionnaires, School Attachment Questionnaire (SAQ) to measure teacher interaction, Rosenberg of Self-Esteem Scale to measure self-esteem, and perception on baby dumping behavior questionnaire to measure the dependent variable. Results showed that self-esteem correlates with perception on baby dumping behavior. In fact, the results also showed teacher interaction are not correlated with perception on baby dumping behavior among secondary school students from various ethnic groups in Sabah. Besides, there was no significant difference in the perception on baby dumping behavior among ethnic group students. Implications of the study were discussed.